Mathematics Teacher’s Scaffolding Patterns Applied to Cooperative Learning Settings to Facilitate Students’ Problem Solving - Utomo, Dwi Priyo; Irawati, Nurul; Kamil, Tika R (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This current research was aimed at analyzing and describing teacher’s scaffolding patterns applied to cooperative learning setting to help students solve mathematical problems. This research was designed qualitatively, recruiting a mathematics teacher of the eighth grade as the subject. Further, the instruments used to carry out the research comprised a test with HOTS questions, observation sheet, and interview guide. To identify the teacher’s scaffolding patterns, the target students were required to work on the HOTS test. Afterwards, they were grouped based on the level of difficulty they faced during working on the test. Next, the teacher provided the students with the scaffolding based on the students’ needs in each of the created groups. This research indicated that the scaffolding given to the group of students with no difficulty in solving the problem only covered a reviewing component. Meanwhile, to the group with the difficulty in executing the plans as arranged, the scaffolding comprised explaining, restructuring, and developing conceptual thinking components. At last, to the group with a sole ability to understand the problem, the whole components of scaffolding were of great necessity, including environmental provisions, explaining, reviewing, restructuring, and developing conceptual thinking.Tujuan dari penelitian ini adalah untuk menganalisis dan mendeskripsikan pola scaffolding guru pada setting pembelajaran kooperatif untuk membantu siswa memecahkan masalah. Penelitian ini adalah penelitian kualitatif dengan subjek guru matematika kelas VIII. Instrumen yang digunakan dalam penelitian ini adalah lembar tes soal HOTS, lembar observasi dan pedoman wawancara. Untuk mengetahui pola scaffolding guru, siswa diminta untuk mengerjakan tes HOTS. Kemudian siswa dikelompokkan sesuai dengan tingkat kesulitan yang dialami saat mengerjakan soal tersebut. Selanjutnya guru memberikan scaffolding sesuai dengan kebutuhan siswa pada masing-masing kelompok. Hasil penelitian ini menunjukkan bahwa scaffolding pada kelompok siswa yang tidak mengalami kesulitan dalam menyelesaikan masalah, hanya pada komponen reviewing. Scaffolding pada kelompok siswa yang mengalami kesulitan pada tahap mengerjakan sesuai rencana, pada komponen explaining, restructuring dan developing conceptual thinking. Siswa yang hanya mampu memahami masalah, scaffolding yang diperlukan pada semua komponen yaitu environmental provisions, explaining, reviewing, restructuring dan developing conceptual thinking.